EFFECTS OF THERMAL CONDUCTIVITY OF FLUID ON FREE CONVECTION FLOW ALONG A VERTICAL FLAT PLATE WITH TRANSVERSE CONDUCTION (Journal of Mechanical Engineering, 2015)
This paper reports the effects of transverse conduction variation with thermal conductivity on freeconvection flow along a vertical flat plate. The governing equations with associated boundary conditions reduceto local non-similarity boundary layer equations for this phenomenon are converted to dimensionless forms usinga suitable transformation. The transformed non-linear equations are then solved using the implicit finitedifference method together with Keller-box technique. Numerical results of the velocity and temperature profiles,skin friction and surface temperature profiles for different values of the thermal conductivity parameter, thePrandtl number and the transverse conduction variation parameters are presented graphically. Detaileddiscussion is given for the effect of the aforementioned parameters. Mentionable effect is found in skin friction andsurface temperature for the transverse conduction variation parameter.